CRISPR guide RNA design for research applications. (22nd June 2016) - Mohr, Stephanie E.; Hu, Yanhui; Ewen‐Campen, Benjamin; Housden, Benjamin E.; Viswanatha, Raghuvir; Perrimon, Norbert
Abstract : The rapid rise of CRISPR as a technology for genome engineering and related research applications has created a need for algorithms and associated online tools that facilitate design of on‐target and effective guide RNAs (gRNAs). Here, we review the state of the art in CRISPR gRNA design for research applications of the CRISPR‐Cas9 system, including knockout, activation, and inhibition. Notably, achieving good gRNA design is not solely dependent on innovations in CRISPR technology. Good design and design tools also rely on availability of high‐quality genome sequence and gene annotations, as well as on availability of accumulated data regarding off‐targets and effectiveness metrics. Abstract : The rise of CRISPR‐Cas9 as a research technology created a need for bioinformatics approaches that facilitate design of guide RNAs (gRNAs), including for knockout, activation, and other approaches. A good design pipeline includes selection and filtering of gRNAs based on our growing knowledge of CRISPR‐Cas9 systems; relies on high‐quality genome sequence and gene annotations; and incorporates data from experimental tests.